Prevalence and causes of blindness and diabetic retinopathy in Southern Saudi Arabia - Hajar, Saad (Saudi Med J, 2015)
OBJECTIVES: To determine the prevalence and causes of blindness and diabetic retinopathy (DR) in Jazan district, Southern Saudi Arabia. METHODS: Using the standardized Rapid Assessment for Avoidable Blindness (RAAB) and DR cross-sectional methodology, 3800 subjects were randomly selected from the population of ≥50 years of age in Jazan, Saudi Arabia between November 2011 and January 2012. Participants underwent screening comprised of interview, random blood glucose test, and ophthalmic assessment including visual acuity (VA) and fundus examination. Among participants with VA <6/18 in either eye, the cause(s) of visual impairment was determined. Participants were classified as diabetic if they had previous diagnoses of diabetes, or random blood glucose >200 mg/dl. Diabetic participants were assessed for DR using dilated fundus examination. All data were recorded using the RAAB + DR standardized forms. RESULTS: The prevalence of bilateral blindness <3/60 was 3.3% (95% confidence interval [CI]: 2.74 - 3.90). Cataract was the leading cause of blindness (58.6%); followed by posterior segment diseases (20%), which included DR (7; 3.3%). The prevalence of diabetes mellitus (DM) was 22.4%, (95% CI: 21.09 - 23.79), among them; 27.8% had DR. The prevalence of sight-threatening DR was 5.7%. CONCLUSION: The prevalence of DM and the corresponding proportion of DR in this region is lower than that reported in other regions of Saudi Arabia. However, the prevalence of blindness not related to DR is relatively higher than the other studies.